2016
DOI: 10.1160/th15-06-0462
|View full text |Cite
|
Sign up to set email alerts
|

Zinc promotes clot stability by accelerating clot formation and modifying fibrin structure

Abstract: Zinc released from activated platelets binds fibrin(ogen) and attenuates fibrinolysis. Although zinc also affects clot formation, the mechanism and consequences are poorly understood. To address these gaps, the effect of zinc on clot formation and structure was examined in the absence or presence of factor (F) XIII. Zinc accelerated a) plasma clotting by 1.4-fold, b) fibrinogen clotting by 3.5- and 2.3-fold in the absence or presence of FXIII, respectively, c) fragment X clotting by 1.3-fold, and d) polymerisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 32 publications
2
40
0
1
Order By: Relevance
“…Based on the in vitro effects of zinc that reduces fibrin clot stiffness, it was suggested that zinc released from activated platelets may modulate clot strength and stability in cooperation with Factor XIIIa. Fibrin elasticity can be modulated by other physical influences (Kotlarchyk et al 2011; Munster et al 2013) or biochemical modifications as well as by blood components and cells incorporated into the fibrin network (Rojas et al 2009; Weigandt et al 2012; Lauricella et al 2013; Jansen et al 2013; Henderson et al 2015). …”
Section: 5 Fibrin Mechanical Properties and Their Structural Originsmentioning
confidence: 99%
“…Based on the in vitro effects of zinc that reduces fibrin clot stiffness, it was suggested that zinc released from activated platelets may modulate clot strength and stability in cooperation with Factor XIIIa. Fibrin elasticity can be modulated by other physical influences (Kotlarchyk et al 2011; Munster et al 2013) or biochemical modifications as well as by blood components and cells incorporated into the fibrin network (Rojas et al 2009; Weigandt et al 2012; Lauricella et al 2013; Jansen et al 2013; Henderson et al 2015). …”
Section: 5 Fibrin Mechanical Properties and Their Structural Originsmentioning
confidence: 99%
“…These include the concentrations of procoagulants, anticoagulants, fibrin(ogen)-binding proteins, molecules 1220 , and metal ions 21,22 , as well as contributions of blood and vascular cells, and cell-derived microvesicles 2330 , and presence of blood flow 31,32 (Figure 2). Many of these mechanisms have been reviewed.…”
Section: Fibrin Formation Structure and Stabilitymentioning
confidence: 99%
“…Clot rigidity correlates strongly with the structure of fibrin networks, namely with fiber size and branching that varied upon conditions of clotting [52]. Based on the in vitro effects of zinc that reduces fibrin clot stiffness, it was suggested that zinc released from activated platelets may modulate clot strength and stability in cooperation with factor XIIIa [53]. Fibrin polymerized under continuous mechanical perturbation was shown to form a rigid clot with dramatically altered viscoelastic properties [54].…”
Section: Non-linear Elasticity and High Deformability Of Fibrinmentioning
confidence: 99%